GROUP PLAY THERAPY ON CHILDREN'S WITH THALASEMIA SELF-CONCEPT IN BOGOR : GROUP PLAY THERAPY ON CHILDREN'S WITH THALASEMIA SELF-CONCEPT IN BOGOR - Yuliastati, Yuliastati; Pursitasari, Ita; Halimah, Siti Nur; Sahat, Camalia S (Jurnal Kesehatan Masa Depan, 2022)
Thalassemia is one of the most common genetic blood disorders suffered by people in the world. According to WHO (2012), approximately 7% of the world's population has the thalassemia gene where the highest incidence of up to 40% of cases is in Asia. According to IDAI data for 2016, the prevalence of thalassemia major in Indonesia was 9,121 people. Based on data from the Association of Indonesian Thalassemia Parents (POPTI) in 2018 there were 9,028 (Ministry of Health, 2019). In Bogor City itself, based on the POPTI report, the number of children with thalassemia is 400 people. The aim of the study was to obtain an overview of the effect of group play therapy on the self-concept of children with thalassemia in Bogor City. Quantitative research method with quasi-experimental method pre test–post test control group design to compare the results of the intervention of two groups: the intervention group, namely the Thalassemia children who received group play therapy and the control group, namely the Thalassemia children who did not receive group play therapy. The number of research samples was 35 respondents for each intervention and control group. The aim of the study was to obtain an overview of the effect of group play therapy on the self-concept of children with thalassemia in Bogor City. Data analysis was performed using univariate and bivariate. The results showed that there was a significant effect between group play therapy (TBK) in thalassemia children on the self-concept of children with thalassemia in Bogor City with P Value = 0.000 at alpha <0.05. The conclusion is that group play therapy (TBK) has a significant effect on the self-concept of children with thalassemia with P value = 0.000, at α = 0.05. There is a significant difference in the mean self-concept of thalassemia children between the intervention group and the control group with a P value = 0.000, meaning at alpha 0.05. Keywords: Group Play Therapy; Self-concept; Thalassemia